2018
DOI: 10.1101/324301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular Crowding Influences Extrusion and Proliferation to Facilitate Epithelial Tissue Repair

Abstract: Epithelial wound healing requires a complex orchestration of cellular rearrangements and movements to restore tissue architecture and function after injury. While it is well-known that mechanical forces can affect tissue morphogenesis and patterning, how the biophysical cues generated after injury influence cellular behaviors during tissue repair is not well understood.Using time-lapsed confocal imaging of epithelial tissues in living zebrafish larvae, we provide evidence that localized increases in cellular c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…These data suggested that BATF preferentially heterodimerizes with other bZIP transcription factors to form activating or suppressive transcription factor complexes in the overall context of ILC2s activation. The positively regulated genes were enriched for genes involved in cell projection morphogenesis, regulation of cell projection organization, and positive regulation of epithelial cell proliferation, all of which are pathways involved in wound healing and tissue repair as reported previously (42,45,46). In contrast, genes negatively regulated by BATF were enriched for genes involved in the inflammatory response, myeloid leukocyte activation, and Neu migration (Fig.…”
Section: Batf Promotes Expression Of Tissue Repair Genes and Represse...supporting
confidence: 76%
“…These data suggested that BATF preferentially heterodimerizes with other bZIP transcription factors to form activating or suppressive transcription factor complexes in the overall context of ILC2s activation. The positively regulated genes were enriched for genes involved in cell projection morphogenesis, regulation of cell projection organization, and positive regulation of epithelial cell proliferation, all of which are pathways involved in wound healing and tissue repair as reported previously (42,45,46). In contrast, genes negatively regulated by BATF were enriched for genes involved in the inflammatory response, myeloid leukocyte activation, and Neu migration (Fig.…”
Section: Batf Promotes Expression Of Tissue Repair Genes and Represse...supporting
confidence: 76%
“…Zebrafish are an ideal system for investigating the relationship between gradient disruption and wound healing, due to their power as a model organism and their aqueous, freshwater lifestyle. The excellent optical properties of larval zebrafish epidermis and the availability of genetic tools for live fluorescence imaging have made zebrafish larvae a prominent model system for understanding the rapid mechanisms of wound repair in the first few minutes after injury (Enyedi et al, 2013; Franco et al, 2019; Gault et al, 2014; Kennard and Theriot, 2020; Poplimont et al, 2020; Yoo et al, 2012). The zebrafish larval epidermis is composed of two layers of cells: a superficial layer that maintains barrier function via tight junctions, and a basal layer of proliferative cells that can migrate on the basement membrane/extracellular matrix (ECM) and can perform other tissue maintenance functions, including phagocytosis of apoptotic cells (Arora et al, 2020; Rasmussen et al, 2015; Sonawane et al, 2005) ( Figure 1A-B ).…”
Section: Introductionmentioning
confidence: 99%
“…The zebrafish larval epidermis is composed of two layers of cells: a superficial layer that maintains barrier function via tight junctions, and a basal layer of proliferative cells that can migrate on the basement membrane/extracellular matrix (ECM) and can perform other tissue maintenance functions, including phagocytosis of apoptotic cells (Arora et al, 2020; Rasmussen et al, 2015; Sonawane et al, 2005) ( Figure 1A-B ). Previous work has shown that the two layers respond to injury using distinct wound closure mechanisms: superficial cells assemble an actomyosin purse string around the wound margin, while basal cells actively migrate towards the wound using actin-rich lamellipodia (Franco et al, 2019; Gault et al, 2014). Crucially, zebrafish are freshwater organisms capable of withstanding more than 20-fold osmotic gradients between interstitial fluid and the surrounding environment (Krens et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo work has suggested that re-epithelialization occurs in a dynamic mechanical environment, yet many studies of the biophysical mechanisms driving wound closure have occurred outside of the relevant tissue context. Depending on the species of animal and the type of injury, the initial wound and subsequent healing process can lead to changes in tissue tension, extracellular matrix composition, and cell crowding (Evans et al, 2013; Franco et al, 2019; Singer & Clark, 1999). In contrast, studies of cultured cells on plastic or glass surfaces provide far simpler environments.…”
Section: Introductionmentioning
confidence: 99%